Cushioning the Blow: How Firms Target Credit Ratings - Liu, Tim; Shivdasani, Anil (The Review of Corporate Finance Studies, 2026)
Abstract While firms manage their capital structure to target credit ratings, how targeting impacts capital structure decisions is not well understood. We hypothesize that firms engage in ratings cushioning by preserving a leverage buffer against rating downgrades. We show that ratings cushions are sizable in magnitude. Following plausibly exogenous increases in cushion, firms increase leverage to consume their newfound cushion particularly when they have attractive investment opportunities and are less exposed to earnings shocks. These findings suggest that ratings cushioning restrains firms from pursuing otherwise more aggressive capital structure and investment choices. (JEL G31, G32)